Elimination of Secondary Neutrons from Laser Proton-Boron Fusion. (8th April 2021) - Hora, Heinrich; Eliezer, Shalom; Nissim, Noaz
Abstract : For low carbon energy generation, a very large exchange of electricity generators is existentially vital within the next number of years by power stations preferably at considerably low cost than the present installations. When considering the million times higher nuclear energy per reaction than chemical, the usual hydrogen fusion with abundant boron fuel is used for environmentally clean electricity generators. Instead of usually needed ignition temperatures of hundreds of million degrees Celsius, it is possible to use nonthermal ignition pressures from now available CPA laser pulses. In this non-LTE scheme, there is no need for high compression, the medium of hydrogen-boron-11 temperatures is low, and therefore the bremsstrahlung losses practically do not exist. The neutron, created by secondary reactions, elimination device includes tin and is arranged such that the neutrons are brought to nuclear reactions with the tin. We suggest adding the tin that has proven to be particularly advantageous because of its high effective cross section, and the neutron reactions with tin transform the tin nuclei into stable nuclei with a higher atomic weight.